ANALISIS TRANSPARANSI DAN AKUNTABILITAS DANA DESA SEBAGAI PENGUATAN BADAN USAHA MILIK DESA (Studi Badan Usaha Milik Desa Tirta Mandiri Ponggok Klaten) - Pardi Pardi; Budi Istiyanto (ITB AAS INDONESIA Surakarta, 2020)
This research’s objectives are (1) to analyze communities’ response on Tirta Mandiri Village-Owned Enterprises (BUMDes)’ successful programs, (2) to analyze the transparency of village fund utilization as an empowering effort of BUMDes Tirta Mandiri for village’s self-reliance, (3) to analyze the accountability of village fund utilization for village’s self-reliance. The qualitative research used Focus Group Discussion, observation, interview, documentation, and physical devices method to collect the data. The data collection process used interview procedures with a self-arranged questionnaire. The data were analyzed using the interactive model which comprises data reduction, data presentation, concluding, and verification followed by the data collection process. The qualitative data were validated using source triangulation. The result of this research shows that (1) there are two kinds of response following the success of BUMDes Tirta Mandiri, they are communities who agree on the programs and the ones who do not, (2) the utilization of village fund as BUMDes Tirta Mandiri’s strengthening needs transparency on its process. The utilization of village funds as BUMDes Tirta Mandiri’s strengthening on the village’s self-reliance needs to be accountable for its accountability report. Keywords: Transparency, Accountability, Village Fund, BUMDes’ Strengthening